2000
DOI: 10.1111/j.1572-0241.2000.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining The Role of Fiberoptic Sigmoidoscopy in The Investigation of Patients Presenting With Bright Red Rectal Bleeding

Abstract: In young persons with bright red rectal bleeding, fiberoptic sigmoidoscopy may prove to constitute appropriate initial investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
4
22
1
1
Order By: Relevance
“…Stated differently, an 80-yr-old patient with rectal bleeding or a positive fecal-occult blood test is considerably more likely to have cancer than a person aged Ͻ50 yr with the identical symptom or finding. This relationship was again confirmed by Canadian investigators in a study (1) in this issue of the American Journal of Gastroenterology, who concluded that patients aged Ͻ55 yr with nonmassive rectal bleeding can be safely evaluated initially by flexible sigmoidoscopy.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Stated differently, an 80-yr-old patient with rectal bleeding or a positive fecal-occult blood test is considerably more likely to have cancer than a person aged Ͻ50 yr with the identical symptom or finding. This relationship was again confirmed by Canadian investigators in a study (1) in this issue of the American Journal of Gastroenterology, who concluded that patients aged Ͻ55 yr with nonmassive rectal bleeding can be safely evaluated initially by flexible sigmoidoscopy.…”
supporting
confidence: 51%
“…I also admit that, although my approach is partly to "reassure the patient," as discussed by Rosendaal et al (1), it is also clearly to reassure myself. Anecdotally, my impression from reviewing malpractice cases is that delays in diagnosis occur commonly in young people with symptomatic colorectal cancer.…”
mentioning
confidence: 99%
“…Flexible or rigid rectosigmoidoscopy is the usual method of investigation performed to identify and treat active intrarectal bleeding. 10 In hospitals where endoscopy fails to locate the origin of the bleeding or to control the active hemorrhage and where continued hemorrhage can not be investigated by angiography, emergency surgery is an option. However these surgical procedures may be complicated by significant morbidity (sphincter lesion, fistula, abscess, local infection or septicemia) or even mortality in patients sustaining hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Constrained capacity for colonoscopy screening has been the topic of recent articles and symposiums [4][5][6]. In a typical endoscopy center, there are many indications for colonoscopy, including screening, surveillance, symptoms, a positive FOBT, and iron deficiency anemia [3,[7][8][9][10][11]. In light of the limited capacity, targeting Financial support: none.…”
Section: Introductionmentioning
confidence: 97%